Preconditioning strategies to enhance physical performance on the day of competition - Kilduff, L. P.; Finn, C. V.; Baker, J. S.; Cook, C. J.; West, D. J. (International Journal of Sports Physiology and Performance, 2013)
Sports scientists and strength and conditioning professionals spend the majority of the competition season trying to ensure that their athletes` training and recovery strategies are appropriate to ensure optimal performance on competition day. However, there is an additional window on the day of competition where performance can be acutely enhanced with a number of preconditioning strategies. These strategies include appropriately designed warm-up, passive heat maintenance, postactivation potentiation, remote ischemic preconditioning, and, more recently, prior exercise and hormonal priming. The aim of this review was to explore the potential practical use of these strategies and propose a theoretical timeline outlining how they may be incorporated into athlete`s precompetition routine to enhance performance. For the purpose of this review the discussion is confined to strategies that may enhance performance of short-duration, high-intensity sports (eg, sprinting, jumping, throwing).